A new model for the optimization of periodic inspection intervals with failure interaction: A case study for a turbine rotor. (October 2017) - Rezaei, Esmaeil
Highlights: Considering both minimal and perfect repairs simultaneously in reliability model. Considering both minimal and perfect repairs simultaneously in cost model. Considering failure interaction between components. Abstract: Inspection is one of the important activities to detect and fix failures in repairable system. Optimization of inspection intervals has critical role in maintenance cost and operating system. When a component fails, it is renewed or repaired. A great deal of periodic inspection research is for hidden failure and considered one of the perfect (renew) and minimal repair policies. In literature, the lack of simultaneous consideration of both perfect and minimal repair in reliability model has been observed. This study presents new reliability model by synchronous consideration of both minimal and perfect repair. As well as, the expected total maintenance cost is presented and modeled to figure out the optimal inspection interval. The proposed model is more comprehensive model in reliability evaluation and can be applied in different pertinent problems. The model is applied to steam turbine system which the rotor considered as soft component and filter as hard component. The result revealed that the system should be inspected every 12 month.